Promoção de vendas não monetária e seus efeitos na intenção de compra e na escolha da marca de serviços financeiros - Boschetti, Rochele Bagnolini (2012)
This study examines the effects of premium-based non-monetary sales promotion in purchase intentions and brand choice in the financial services market, based on the premium attractiveness. This research is motivated by the lack of studies involving sales non-monetary promotions in general, in the country and also on the international scene. The research is justified in the service sector because most of research being carried out in the market for consumer goods. The study has an exploratory and experimental stage with the completion of two experiments involving 655 undergraduates in the course of administration of a private university located in Porto Alegre/RS. Regarding to purchase intention, the assumption is that non-monetary sales promotions with premiums attractive affect the construct positively. On brand choice, the hypothesis postulates that non-monetary sales promotions with premiums attractive increase the likelihood of brand choice promoted. The results show that nonmonetary sales promotions premiums based on impact on consumer behavior according to the hypotheses proposed by the research, demonstrating that the premiums attractiveness is an important variable in the evaluation of a promotional offer that aims to increase the intention purchase and motivate the selection of brand. At the end of the paper is presented the findings of the study on the contribution to advance the theory in non-monetary sales promotions as well as managerial implications that contribute to marketing professionals with promotion strategies premiums-based so that resources are used in activities that stimulate consumer interest. Finally, future research are presented in order to motivate other researchers to search for new knowledge in the area.